Changes in Muscle Activation During and After a Shoulder-Fatiguing Task: A Comparison of Elite Female Swimmers and Water Polo Players - King, Savannah; Dong, Lily; Caron, Michelle; Côté, Julie N. (Frontiers in Sports and Active Living, 2022)
This study compared female athletes with different aquatic sports expertise in their neuromuscular activation before, during, and after a shoulder internal rotation fatigue protocol. Eleven water polo players, 12 swimmers, and 14 controls completed concentric maximal voluntary external and internal shoulder rotations before and after a fatigue protocol consisting of concentric internal rotations at 50% of maximal voluntary contraction for at least 3 min or until reporting a rating of perceived effort RPE of 8/10 or higher. Muscle activation was measured for the maximal voluntary contractions, as well as for the first (T1), middle (T2), and third (T3) minute of the fatigue protocol using surface electromyography (EMG) on pectoralis major, anterior and posterior deltoid, upper and middle trapezius, and latissimus dorsi. Intramuscular EMG was used for supraspinatus, infraspinatus, and subscapularis. Pre-fatigue internal rotation torque was significantly correlated with shorter task duration (r = −0.39, p = 0.02), with water polo players producing significantly greater torque than controls but having significantly lower endurance. Swimmers demonstrated decreased latissimus dorsi activation at T3 compared to T2 (p = 0.020, g = 0.44) and T1 (p = 0.029, g = 0.74), differing from water polo players and controls who exhibited increased agonist activation and decreased activation of stabilizers. Comparing the pre-fatigue to the post-fatigue maximal shoulder rotations, water polo players had decreased activation in subscapularis (p = 0.018, g = 0.67); all groups had decreased activation in latissimus dorsi (p < 0.001), though swimmers demonstrated a large effect (g = 0.97); and controls had decreased activation in supraspinatus (p = 0.005, g = 0.71). Together, these results suggest that sports expertise may be associated with different muscle activation both while and after fatigue is induced. Further research should continue to explore sports-specific patterns of muscle recruitment and fatigue adaptations, as well as if certain strategies are adaptive or maladaptive. This may have important consequences for injury prevention among athletes who perform repetitive overhead movements in their sports and who are susceptible to overuse injuries.